2015
DOI: 10.1080/10408398.2014.941457
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics: The Scientific Evidence in the Context of Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) generally comprises Crohn's disease (CD) and ulcerative colitis (UC), and their main characteristic is the intestinal mucosa inflammation. Although its origin is not yet fully known, there is growing evidence related to genetics, intestinal microbiota composition, and the immune system factors such as precursors for the initiation and progression of intestinal conditions. The use of certain probiotic microorganisms has been touted as a possible and promising therapeutic approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 116 publications
0
31
0
9
Order By: Relevance
“…Fermented milks and probiotics appear to be very promising for IBD patients since several studies have shown that these can possess anti‐inflammatory properties (de Moreno de LeBlanc and LeBlanc ; Celiberto et al . ; Wasilewski et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fermented milks and probiotics appear to be very promising for IBD patients since several studies have shown that these can possess anti‐inflammatory properties (de Moreno de LeBlanc and LeBlanc ; Celiberto et al . ; Wasilewski et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, probiotics, used as dietary supplements or pharmaceutical preparations, have been evaluated as an alternative (Celiberto et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Изменения в качественном и/или количественном составе микробиоты кишечника и дисбаланс микрофлоры (дисбиоз) могут приводить к клинически значимым негативным последствиям для процесса пищеварения, снижению детоксикационной функции печени и развитию ряда заболеваний, включая воспалительные заболевания кишечника (ВЗК) и болезни печени [3][4][5].…”
Section: микробиота кишечникаunclassified
“…Probiotics have been widely studied because of their ability to modulate gut microbiota and immunological systems in both humans and livestock [1,2], where they serve as prophylaxes and for therapeutic purposes in clinical and veterinary practices [3][4][5]. Thus, probiotics are considered as an emerging, safe and viable alternative to antibiotics, for increasing the performance of farm animals.…”
Section: Introductionmentioning
confidence: 99%